Outcome of a semi-closed mixed intensive care unit in a medical college: A prospective observational study - Keyal, Niraj Kumar; Mishra, Jeetendra Kumar; Mahato, Rupesh; Gupta, Gaurav; Kanu, Ujjawal Shah; Gupta, Suchitra; Sharma, Sachit (Journal of Nepalese Society of Critical Care Medicine, 2025)
Background and aims: The patients with the most severe illnesses are admitted in intensive care unit (ICU). This study was conducted to explore the outcome of patients admitted to the intensivist led semi-closed mixed ICU of a medical college in Nepal. Methods: Five hundred and forty-two patients with age 18 years or above, admitted to the level three ICU of National Medical College over one year period was included in the study. The outcome of the patient was defined as discharge to ward, death, leave against medical advice, or do not resuscitate. Results: Out of 542 patients admitted in the ICU during the study period, 444 (82%) patients were discharged to the ward, 63 (12%) died, 24 (4%) left against medical advice and 11 (2%) gave do not resuscitate orders. Mortality in intubated and trauma patients was 25.0% and 4.7% respectively. Conclusion: This study shows favourable results in terms of patient outcome in an intensivist led semi-closed mixed ICU of a medical college in Nepal.